A theoretical model of strategic management of family firms. A dynamic capabilities approach. Issue 3 (September 2016) - Barros, Ismael; Hernangómez, Juan; Martin-Cruz, Natalia
Highlights: We combine the dynamic capabilities approach with the involvement and essence approaches. Family involvement and family essence influence learning in the family firm. Dynamic familiness explains strategic management in family firms. Dynamic familiness capabilities generate strategic adjustment in the family firm. Abstract: A key issue of family firms' strategic management is to determine the factors that are specific to family firms. Despite theoretical and empirical progress in understanding the mechanisms behind strategic decision making in family firms, there is still no strategic management theory for family firms. To address this gap, we adapt the dynamic capabilities approach to family firms by developing a theoretical model that attempts to serve as a framework for helping family firms in the strategic decision making process. The model is based on the concept of familiness and family learning mechanisms (knowledge accumulation, integration, codification and socioemotional wealth preservation) suggesting that the interplay of the two impacts on the efficient strategic management of family firms. Theoretical and practical implications are discussed.